A Study of Agoraphobia in The Scarlet Letter by Nathaniel Hawthorn - Ahmad, Hedayat Muhamad (Raden Intan State Islamic University of Lampung, Indonesia, 2023)
The core objective of this paper is to argue the term of agoraphobia and applying it to Nathaniel Hawthorne’s superb work The Scarlet Letter. This novel is an imaginative piece of literary work which was written in the age of puritanism to exhibit the reality of social, cultural and religious struggles of that age via the performance of characters, phobia is a sort of fear and it is a condition that each character possibly faces it explicitly or implicitly throughout the story of the novel, as it is of many sorts, agoraphobia is one of them which simply carries the meaning of being scared of market place and crowded areas, Hester Prynne is the one of the characters of The Scarlet Letter , who has such a sort fright and is socially banished because of her disgusted deed which was adultery ,the symbol of “A” was hanged on the chest of her daughter, who was the outcome of Hester’s act of adultery, caused her to have a non-stopping psychological pain that separated her in a way that she saw death in every moment of her life. She was dehumanized and deprived from the whole social contacts, events and activities while her partner who was Arthur Dimmesdale had a missing identity.